Accelerated Fenton-like kinetics by visible-light-driven catalysis over iron(iii) porphyrin functionalized zirconium MOF: effective promotion on the degradation of organic contaminants. Issue 8 (17th July 2019) - Wang, Lei; Jin, Pengxia; Duan, Shuhua; Huang, Jingwei; She, Houde; Wang, Qizhao; An, Taicheng
Abstract : Fe III –TCPPCl-incorporated UiO-66 MOF could reliably achieve both photocatalysis and a Fenton-like reaction under visible light, with effective degradation against organic pollutants. Abstract : Ultraviolet (UV)-light or a cocatalyst ( e.g., chelating agents) is commonly used to promote a Fenton-like technique in the treatment of organic contaminants in wastewater. However, the energy costs for generating UV and the poor recyclability of the iron (Fe)-based catalyst/cocatalyst remain primary concerns for their further implementation. Herein, we present a visible-light-driven collaborative process comprising photocatalysis and Fenton-like reaction that are both conducted using a derivative of a zirconium (Zr)-based metal–organic framework (UiO-66 MOF), in which Fe(iii ) tetra(4-carboxylphenyl)porphyrin chloride (Fe III –TCPPCl) is coordinated in the pore of UiO-66. The mixed ligand Fe III –TCPPCl not only plays the role of a photosensitizer that fosters light absorption and suppresses the recombination of photo-induced carriers over the integrated structure, Fe III –TCPPCl⊂UiO-66 (FTU), but also acts as a potential iron-based catalyst for decomposing hydrogen peroxide (H2 O2 ) to engender oxidative hydroxyl radicals (˙OH). Furthermore, besides achieving virtually 100% decomposition of a surrogate pollutant, rhodamine B (RhB), compared with 51% achieved by photolysis alone within 60 min, introducing H2 O2 into the visible-light irradiating system could also promote the mineralization of RhB, as indicated by a 15.5% increment in chemical oxygen demand (COD) removal. The photo-excited electrons partially participate in the reduction of the immobilized Fe III –TCPPCl into Fe II –TCPPCl, and therefore greatly accelerate the Fenton-like reaction. Moreover, the structural similarity of FTU to the robust parent UiO-66 guarantees its reliable recycling performance with respect to degradation over four times.